2006
DOI: 10.1021/ja062580r
|View full text |Cite
|
Sign up to set email alerts
|

A Combined SAXS/WAXS/XAFS Setup Capable of Observing Concurrent Changes Across the Nano-to-Micrometer Size Range in Inorganic Solid Crystallization Processes

Abstract: Crystalline inorganic solids show intriguing properties of importance in many technological applications, such as ferromagnetism, semiconductivity, gas sensing, and catalysis. A great deal of attention has been and continues to be focused on understanding why these materials possess these properties. When such phenomena are fundamentally understood, it becomes possible to improve their performance, and this can potentially lead to the development of new "designer" materials to meet the challenges of the future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 18 publications
2
68
0
5
Order By: Relevance
“…These results are interesting as the authors propose experimental evidence that the formation of chain-like species (e.g. Loiseau et al 49 WAX study) are indeed directly involved in a chain formation mechanism of AlPOs as proposed by Oliver et al 50 Similar measurements were performed by Beale et al 67 on ZnAPO-34, with an even closer match between the SAXS and Scherrer particle size determinations (B12 nm), indicating size retention during crystallization and a similar (but this time two stage) crystallization mechanism was proposed. Most importantly, however, this work discussed the role of the Zn 2+ ions which appear to act as both nucleating and structure directing agents-an observation latterly confirmed by the in situ Raman measurements of the organic template conformation performed by O'Brien et al 70 Most recently Simmance et al 71 again utilized combined XAS/WAXS to examine CoAPO-5 formation.…”
Section: Combined Technique Gel Studiessupporting
confidence: 61%
See 1 more Smart Citation
“…These results are interesting as the authors propose experimental evidence that the formation of chain-like species (e.g. Loiseau et al 49 WAX study) are indeed directly involved in a chain formation mechanism of AlPOs as proposed by Oliver et al 50 Similar measurements were performed by Beale et al 67 on ZnAPO-34, with an even closer match between the SAXS and Scherrer particle size determinations (B12 nm), indicating size retention during crystallization and a similar (but this time two stage) crystallization mechanism was proposed. Most importantly, however, this work discussed the role of the Zn 2+ ions which appear to act as both nucleating and structure directing agents-an observation latterly confirmed by the in situ Raman measurements of the organic template conformation performed by O'Brien et al 70 Most recently Simmance et al 71 again utilized combined XAS/WAXS to examine CoAPO-5 formation.…”
Section: Combined Technique Gel Studiessupporting
confidence: 61%
“…The basic experimental setup is demonstrated in Fig. 9 (with examples of the data recorded separately by Grandjean) and, as demonstrated by Beale et al, 67 the cell and setup is flexible enough to allow these measurements to be performed in a single combined experiment. Here the XANES underwent similar changes to Sankar et al, 66 however a detailed analysis of the high quality XAS data revealed more complex variations in the Fourier transform of the EXAFS.…”
Section: Combined Technique Gel Studiesmentioning
confidence: 99%
“…The use of synchrotron light sources has, for a number of decades now, provided a way to examine catalysts under increasingly more realistic conditions [1][2][3][4][5][6]. The continued development of more brilliant and powerful light sources along with improved detectors has more recently allowed for the combination of two and three X-ray based in situ techniques [1,[7][8][9][10][11][12]. Information can now be collected on various parts of the catalyst congruently revealing additional insight into their operation under various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the PDF was not fully Gaussian in shape and this may indicate that asymmetry in the bond length distribution could also have contributed to the observed increase in radius. When they compared the WAXS analyses with the XAS data however, the agreement was not so good although the WAXS and molecular dynamic modeling fitted better (see also examples below in the XAS section and Beale et al, 2006).…”
Section: Examples Of Nucleation and Growth Saxs/waxs Analysismentioning
confidence: 99%